Implementasi Pemikiran Ibnu Sina tentang Sistem Pendidikan Modern di Sekolah dalam Membentuk Akhlak Terpuji Anak Usia Dini - Idhar, Idhar; Sudin, Mahmudin (Jurnal Ilmiah Wahana Pendidikan, 2025)
In this study to examine the implementation of Ibn Sina's thought in the modern education system in schools to form praiseworthy morals in early childhood, Ibn Sina is an Islamic philosopher and scientist who emphasizes the importance of an education system related to intellectual, spiritual and moral values, Ibn Sina's education is very relevant to the needs of education in this modern era which involves directly in early childhood. In this research using qualitative methods with literature studies that produce descriptive data emphasizes the deepening aspects of the data in order to obtain the quality of a study. Ibn Sina's educational thinking in the modern education system has a positive impact on building noble children and forming an Ihsan Kamil person. In this study recommends that there should be a continuity of educators between parents, teachers and good social groups in building a quality educational environment. Translated with DeepL.com (free version)